Meta-analysis the effect of learning strategies on ability advanced mathematical thinking students - A Aristika; D Darhim (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2020)
Mathematical material and mathematical thinking abilities are two things that are constantly evolving, that is, between mathematical material understood through mathematical thinking skills possessed by students need to be further developed through learning mathematical and mathematical material that continues to grow more widely. Therefore, in mathematics learning it is necessary to develop AMT students' abilities. This meta-analysis uses the results of experimental studies regarding the effect of learning strategies on students' AMT abilities. Of the ten research reports, 18 research findings were obtained which were then the subject of this study. This meta-analysis aims to determine the overall effect of learning strategies on students' AMT abilities, as well as the effect of the three aspects found in these experiments, namely the level of education, tools / learning media, and the types of strategies used. The results of the analysis show that learning strategies are effective in improving the ability of AMT students, with the effect of the greatest influence based on the type of learning strategy that is cooperative. Other findings indicate that the learning strategy at the senior secondary level is more effective. Whereas based on learning aids / media it can be seen that student worksheets are more influential.